Purchasing Decisions Through the 4C ​​Marketing Mix (To Customers of The Gade Coffee & Gold Bogor) - Ibnu Muttaqin; Hirayanti Hutabarat (Universitas Binaniaga Indonesia, 2022)
This research purposes to determine the effect of the 4C marketing mix on the purchasing decisions of the customers of The Gade Coffee & Gold Bogor. This research uses a quantitative approach with research data collection through questionnaires. The population in this research were all customers of The Gade Coffee & Gold Bogor and the sample used was 150 respondents with accidental sampling technique. The results showed that partially customer value, cost to customer, convenience and communication had a positive and significant effect on purchasing decisions. Meanwhile, simultaneously, the 4C marketing mix has a positive and significant effect on purchasing decisions.